Whither the ECOWAS free movement protocols? Pandemic nationalism, borders, and migration in West Africa. (November 2022) - Aniche, Ernest Toochi; Iwuoha, Victor Chidubem; Isike, Christopher
Abstract: The Covid-19 pandemic border closure policy and other anti-migrant policies in 2020 have become another basis for flaunting the ECOWAS free movement protocols by member states now referred to as pandemic nationalism. Although not limited to (West) Africa, pandemic nationalism reinforces the inability of ECOWAS to demonstrate supranationalism and ensure harmonization of Covid-19 trans -border policies among its members. Consequently, member states were unilaterally imposing conflicting or uncoordinated Coronavirus border closure policy without recourse to the protocols. Thus, the pandemic border closure policy has only exacerbated pre-existing trajectories which have serious implications for visa-free, border-free, and borderless West Africa as well as cross-border migration. These challenges are often attributed to colonial borders. This article has been able to adequately demonstrate that the Covid-19 pandemic has deepened nationalism which has, in turn, increased violation of ECOWAS free movement protocols through uncoordinated and reprisal border closure in which nationalism has trumped regionalism. The study is essentially qualitative, descriptive, analytical, and empirical.